Future Directions of Reverse Logistics in Gaining Competitive Advantages: A Review of Literature - Rajagopal, Premkumar; Kaliani Sundram, Veera Pandiyan; Maniam Naidu, Babudass (ExcelingTech Publishers, 2015)
Logistics management is known for its complexity, dynamics and uncertainty. The advent of rapid technology development, intense business competition and changing customer needs and requirements, has forced companies to reshape their business model and strategies. Numerous new terms such as Global Supply Chain, Third Party Logistics, Green Logistics, E-Logistics and Reverse Logistics are becoming issues that have to be deal with by all companies, local, multinational and global. Lately Reverse Logistics start to get attention by most of the firms. The purpose of this assignment is to review and identifies clear definition of Reverse Logistics, comparison Reverse Logistics with Forward Logistics in order to have a better understanding and finally future direction of Reverse Logistics in gaining competitive advantages.